A Comparative Study of Mould Base Tool Materials in Plastic Injection Moulding to Improve Cycle Time and Warpage Using Statistical Method / A.A. Raus ...[et al.] - A. Raus, A.; Wahab, M.S.; Ibrahim, M.; Kamarudin, K.; Ahmed, A.; Sa’ude, N. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In the injection molding process, productivity is measured in terms of the molding cycle time and quality is measured as the extent of warpage of moulded parts. In this study, Computer-Aided Engineering was employed through Moldex 3D simulation software to simulate the injection moulding process. The processing parameters such as melt temperature, ejection temperature, mould temperature, injection pressure, packing pressure, injection time, packing time and including the mould tool material were selected to determine the cycle time and warpage of the simulated part. By using Taguchi Method orthogonal arrays, Signal-to-Noise (S/N) ratio and Analysis of Variance (ANOVA), the simulation result of the moulding cycle time and warpage of Tool Steel (P-20), Aluminum Alloy (QC-10), and Copper Alloy (Be-Cu C18000) insert with conventional cooling channels were analyzed. The result of Aluminum Alloy (QC-10) insert was in a good agreement with the result of the Signal-to-Noise (S/N) whereby Aluminum Alloy (QC-10) has been selected as the best setting of combination for cycle time and warpage. The result also shows that by percentage contribution in ANOVA, ejection temperature,mould material and injection pressure has been identified to be the most significant factors in affecting the cycle time because its P value is less than 0.05. Whereby the ejection temperature contributes the most which is 49.87%, followed by mould material 29.22% and injection pressure 11.38%. While for warpage defect, melt temperature, ejection temperature, injection pressure and packing time were the most significant factor on warpage based on its P value is less than 0.05. The factor of melt temperature has the most percentage of contributions which is 24.69%, followed by ejection temperature 20.71%, injection pressure 18.01% and packing time 12.72%.